2021
DOI: 10.1590/1413-8271202126nesp12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between loneliness and mental health indicators in the elderly during the COVID-19 pandemic

Abstract: Social isolation due to the global pandemic influenced not only the way how people interact, but it also brought a huge impact on the population’s mental health, regardless of their age. This study aimed to evaluate the intensity of symptoms of depression and anxiety, perceived stress, levels of loneliness, and psychological well-being in the elderly during social distancing due to the COVID-19 pandemic. The study included 86 elderlies, aged 60 to 90 years old (M=70.95; SD=7.08), living in the southern region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As this was an online survey, several social segments were not included (such as people in situations of social vulnerability). These barriers limit the reach of these people, as they are unable to access the internet, causing involuntary exclusion of these groups and explaining the difference in the pro le of the study sample compared to the Brazilian population 22 .…”
Section: Discussionmentioning
confidence: 99%
“…As this was an online survey, several social segments were not included (such as people in situations of social vulnerability). These barriers limit the reach of these people, as they are unable to access the internet, causing involuntary exclusion of these groups and explaining the difference in the pro le of the study sample compared to the Brazilian population 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, mental health problems in the elderly commonly occur, such as anxiety and social isolation [12], which has an impact on loneliness. In particular, another study on 86 elderly aged 60 to 90 showed that 55.8% had high-stress symptoms, 18.6% anxiety symptoms, 16.3% depressive symptoms, and 5.82% moderate to severe loneliness [13]. Anxiety, changes in sleep patterns [14], [15], eating patterns [16], [17], pressure due to covid [18], difficulty concentrating [19], [20], boredom [21], [22], stress [23], [24], and psychosomatic disorders [25].…”
Section: Introductionmentioning
confidence: 99%